Catastrophic scapular fracture in a stallion - JI, Espil; MA, Quiroga; FA, Uzal (Brazilian Journal of Veterinary Pathology, 2023)
A 4-year-old Thoroughbred stallion suffered a fracture of the left thoracic limb while racing. Because of the poor prognosis, the horse was euthanized.